The Difficult Imported Mismatch Rules: BEPS Action 2 Recommendations - Allen, Christina (2017)
The OECD recommended various rules that countries can adopt to combat hybrid mismatch arrangements in their domestic tax system. However, its success would not come when the integrity measure, namely "imported mismatch rules", does not operate as intended. This article examines how the imported mismatch rules are meant to operate and discusses inherent practical difficulties in the context of Australia, the United Kingdom and the European Union. It is recommended that countries should take a globally coordinated approach to counter such difficulties.